ARTROPODOS ASOCIADOS A LA FLORACION DEL CHIRIMOYO (ANNONA CHERIMOLA MILL.) EN LA LOCALIDAD DE QUILLOTA, QUINTA REGION, CHILE - López Laport, Eugenio; Rojas Dent, Rita (Acta Entomológica Chilena, 2022)
A survey of arlhropods associated with cherimoya flowers (Annona cherimola Mili.) was carried out in the locality of Quillota, Chile. Approximately 55.000 flowers were samplcd in differents comercial orchards. A great diversity of arlhropods were found, being Carpophiliis hemipterus (L.) one of Ihem.